Cystatin C in Evaluating Renal Function in Ureteral Calculi Hydronephrosis in Adults - Weipu Mao; Shenghua Liu; Keyi Wang; Miao Wang; Heng Shi; Qunlong Liu; Meiyu Bao; Bo Peng; Jiang Geng (Karger Publishers, 2019)
Background: Serum cystatin C (CysC) is still becoming used as a marker of renal function but is far from being commonly used worldwide. The purpose of this study was to characterize the ureteral calculi patients with hydronephrosis-caused CysC changes in renal function. Methods: To better reflect the changes of renal function, we constructed models of ureteral obstruction in rats to mimic the hydronephrosis caused by human ureteral calculi. Moreover, our study included 200 patients diagnosed with ureteral calculi in our hospital between June 2017 and 2018. We compared the estimated glomerular filtration rate using different equations based on CysC and/or serum creatinine (SCr). Results: We found that the expression of CysC and SCr increased with the prolonged obstruction time by enzyme linked immunosorbent assay. Moreover, quantitative real-time polymerase chain reaction, Western blot and immunohistochemistry further demonstrated that the expression of CysC increases with the degree of hydronephrosis. Among 200 patients with ureteral calculi, 40 (20.0%) had no hydronephrosis, 110 (55.0%) had mild hydronephrosis, 32 (16.0%) had moderate hydronephrosis and 18 (9.0%) had severe hydronephrosis. As the degree of hydronephrosis increased, the expression of neutrophil percentage, CysC, blood urea nitrogen, SCr and serum uric acid also increased. Multivariate analyses demonstrated that only CysC was an independent risk factor for hydronephrosis (p = 0.003). In addition, CysC and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) CysC equation showed the highest veracity in renal function estimation of patients with hydronephrosis caused by ureteral calculus. Conclusion: For patients with hydronephrosis caused by ureteral calculi, CysC better reflects the changes in renal function, and the CKD-EPI CysC equation has the highest accuracy.